Digital-Based Islamic Religious Education (IRE) Learning Model at Senior High School - Abdul Halik Nasaruddin; St. Wardah Hanafie Das; Suyatno Ladiqi (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
Contemporary learning trends lead to digital implementation. Digitalization of learning has implications for the effectiveness and efficiency of achieving learning objectives. Demand and need for implementing digital-based learning in Moral and Islamic Religious Education (Pendidikan Agama Islam dan Budi Pekerti, PAI dan BP) because the students are millennials. Digital-based learning design includes objectives, teaching materials, digital media, methods, and evaluation (assessment tools). This study aimed to find a digital-based learning model for PAI and BP subjects at senior high schools. This type of research was qualitative. Observation, interviews, and document studies carried out techniques of data collection. Data was collected through various settings, sources, and methods. Data analysis techniques used data condensation, information disclosure, and conclusion. The study results showed that the digital-based Islamic religious learning approach was scientific and student-centered; Islamic religious learning used Google Classroom, assisted by WhatsApp. Teaching materials were designed as power points, pdf books, and videos. The digital learning model with a student-centered approach has several indicators, including interactive digital learning strategies, lecture methods, assignments, simulations, inquiry, and Islamic religious learning-specific scenarios, namely habituation, exemplary, praise, and threats. Learning techniques use WhatsApp, connected to other social media such as Facebook and Instagram. Learning tactics through humor, singing, rhetoric, and surprise. The implications of implementing digital-based learning models can create a learning atmosphere that encourages students to be more interactive, foster creativity, and develop independent learning.